Estudo da composição bioquímica de unhas para o diagnóstico de Diabetes Mellitus por Espectroscopia Raman - (:unkn) unknown (Universidade Brasil, 2021)
The growth of Diabetes Mellitus (DM) is a public health problem with greater prevalence in developing countries. The estimated prevalence of diabetes in people aged 20-79 years has increased from 151 million to 463 million today, with a total forecast of 700 million diabetics by 2045. Hence the importance of an early, non invasive, practical and low-cost diagnosis for DM detection and monitoring. Type II diabetes mellitus (DM2) gradually changes the intrinsic material properties of tissues and their structural integrity, and prolonged hyperglycemia can cause chronic damage to the quality of these tissues. No technique is available to clinically assess altered tissue quality in diabetic patients. However, recent studies suggest that the quality of the nail plate has great potential to assess the secondary complications of DM. Thus, this study aimed to determine the biochemical characteristics of nails of individuals with DM2 through confocal Raman spectroscopy, in addition to identifying the spectral signatures and new DM2 markers in nails. This study is a multicenter clinical study (Universidade Brasil - SP and Fundação Municipal de Saúde de Teresina/PI), comparative, randomized and instrumental with a qualitative approach. For the research, 30 healthy volunteers and 30 DM2 were selected. The collection and evaluation of fragments in the distal region of the nail was carried out. The results obtained demonstrated alterations in different biochemical components, such as: proteins, lipids, amino acids, advanced glycation end products, in addition to alterations in the disulfide bridges, which are important in the stabilization of keratin in the nails. Therefore, due to the possibility of acquiring such information through the evaluation of nails, a simple and easy-to-acquire material, this becomes an important material for analysis, allowing DM and its complications to be detected quickly. In addition, the study also demonstrated that the assessment of nails by confocal Raman spectroscopy is an important technique, which, together with the assessment of nails, can become an important tool in the diagnosis and follow-up of diabetic patients.
Keywords: Espectroscopia Raman Confocal; Diabetes Mellitus; Unhas; Glicação; Engenharia Biomédica (Bioengenharia)